2016
DOI: 10.1080/00140139.2016.1205222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reflex-based self-defence training on police performance in simulated high-pressure arrest situations

Abstract: We investigated the effects of reflex-based self-defence training on police performance in simulated high-pressure arrest situations. Police officers received this training as well as a regular police arrest and self-defence skills training (control training) in a crossover design. Officers' performance was tested on several variables in six reality-based scenarios before and after each training intervention. Results showed improved performance after the reflex-based training, while there was no such effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Proportionality/subsidiarity and resolution seem to improve particularly for skills that require physical contact to hold off the prisoner, such as fending off a hold or grab and striking/punching and kicking. In accordance with this finding, Renden et al (2017) reported improvement in resolution and proportionality of police officers' actions after reflex-based training, indicating that training in primary responses is an important aspect in skills that require physical contact. In contrast, for skills with the aim to avoid contact (e.g.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Proportionality/subsidiarity and resolution seem to improve particularly for skills that require physical contact to hold off the prisoner, such as fending off a hold or grab and striking/punching and kicking. In accordance with this finding, Renden et al (2017) reported improvement in resolution and proportionality of police officers' actions after reflex-based training, indicating that training in primary responses is an important aspect in skills that require physical contact. In contrast, for skills with the aim to avoid contact (e.g.…”
Section: Discussionsupporting
confidence: 75%
“…By stressing representativeness in the test scenarios (test environment), we could determine that training (learning environment) is not yet fully representative for the eventual performance environment (criterion environment; K€ orner . In developing our test sessions and assessment protocol, we borrowed from the methodology of Renden et al (2017) to test self-defence skills of police officers, and we used focus groups with expert instructors to determine which self-defence skills are needed in the work of correctional officers. In this way, we were able to identify the relevant personal, task, and environmental constraints on duty (Davids et al, 2006;Pinder et al, 2011) and develop a representative test protocol to test the relevant practical skills and competencies of correctional officers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Police training based on reflex-based self-defense mechanisms for acting in high-pressure arrest situations has been recently found to improve ASDS [10]. The operational procedures examined in this work may be similarly efficient for this purpose [3].…”
Section: Ijomeh 2020;33(1)mentioning
confidence: 99%